BlueMonarch: A System for Evaluating Bluetooth Applications in the Wild - Smith, Tim; Saroiu, Stefan; Wolman, Alec (Proceedings of the 7th Annual International Conference on Mobile Systems, Applications and Services (MobiSys), 2009)
Despite Bluetooth’s popularity, low cost, and low power requirements, Bluetooth applications remain remarkably unsophisticated. Although the research community and industry have designed games, cell-phone backup, and contextual advertising systems with Bluetooth, few such applications have been prototyped or evaluated on a large scale. Evaluating Bluetooth applications requires recruiting devices in the wild and developing robust software that can adapt to the heterogeneity of these devices. These requirements have limited both the number and the magnitude of the experiments with Bluetooth applications. This paper proposes BlueMonarch, a system for evaluating Bluetooth applications in the wild. BlueMonarch emulates a Bluetooth transfer to any device responding to Bluetooth Service Discovery requests; because many cell-phones, laptops, and PDAs in the wild respond to such probes, BlueMonarch enables quick prototyping of Bluetooth applications in the wild, to hundreds of unmodiﬁed Bluetooth devices. After we present the feasibility and accuracy of BlueMonarch, we use BlueMonarch to evaluate a content delivery system for Bluetooth. With BlueMonarch, we evaluated our system inside a mall and a subway system; we were able to send tens of megabytes of data to hundreds of Bluetooth devices in just a little over an hour.